A Review on the Most Important Medicinal Herbs Native to Iran with Anti-Acetaminophen Toxicity - Mahmoud Mirhosseini (Journal of Global Pharma Technology, 2017)
Acetaminophen is an analgesic and anti- fever drug, which can be toxic in high doses and leads to hepatic and renal injury. Acetaminophen poisoning can cause many complications and injuries in the body including vomiting, diarrhea, malaise, shock, jaundice, and liver failure and in some cases will lead to myocardial and kidney damage. Against all toxic and destructive effects of drugs like acetaminophen, some compounds are found that can partially restrain poisoning of abuse such compounds. In this review article, medicinal plants native to Iran have been reported, which are used to protect acetaminophen toxicity. In this review study, searching the articles with key words such as acetaminophen, hepatotoxicity, herbs, extracts, and essential oils were used. Searching the articles was conducted through databases of income in Iran like Google Scholar, ISI January, MegaIran, and a number of other databases. Medicinal plants including green tea, turmeric, cress, dandelion, and capers are the most important medicinal plants against the toxicity of acetaminophen. It seems that pharmacological bioactive and antioxidants substances obtaining from plant and biological materials are anti- acetaminophen poisoning.Keywords: liver, Toxicity, Acetaminophen, Herbs, Iran.